One-Year Efficacy Testing of Enabling Mothers to Prevent Pediatric Obesity Through Web-Based Education and Reciprocal Determinism (EMPOWER) Randomized Control Trial. (February 2016) - Knowlden, Adam; Sharma, Manoj
Background . The purpose of this study was to evaluate the efficacy of the Enabling Mothers to Prevent Pediatric Obesity through Web-Based Education and Reciprocal Determinism (EMPOWER) intervention at 1-year, postintervention follow-up. Method . A mixed between–within subjects design was used to evaluate the trial. Independent variables included a two-level, group assignment: EMPOWER (experimental intervention) based on social cognitive theory (SCT) as well as a knowledge-based intervention Healthy Lifestyles (active control intervention). Dependent variables were evaluated across four levels of time: baseline (Week 0), posttest (Week 4), 1-month follow-up (Week 8), and 1-year follow-up (Week 60). Dependent variables included five maternal-facilitated SCT constructs (environment, emotional coping, expectations, self-control, and self-efficacy) as well as four child behaviors (minutes of child physical activity, cups of fruits and vegetables consumed, 8-ounce glasses of sugar-sweetened beverages consumed, and minutes of screen time). Null hypotheses implied no significant group-by-time interactions for the dependent variables under investigation. Results . A significant group-by-time interaction for child fruit and vegetable consumption was found in the experimental group ( p = .012) relative to the control group. At 1 year, results suggested an overall increase of 1.847 cups of fruits and vegetables (95% confidence interval = 1.207-2.498) in the experimental group ( p < .001). Analysis suggested changes in the maternal-facilitated home environment accounted for 13.3% of the variance in the change in child fruit and vegetable consumption. Improvements in child physical activity, sugar-free beverage intake, and screen time first detected at 1-month follow-up in both groups were no longer significant at 1-year follow-up. Conclusions . An online family-and-home-based intervention was efficacious for improving child fruit and vegetable consumption. Follow-up booster sessions may assist in maintaining treatment effects.